2016
DOI: 10.1093/ckj/sfw017
|View full text |Cite
|
Sign up to set email alerts
|

Improving clinical skills to support the emotional and psychological well-being of patients with end-stage renal disease: a qualitative evaluation of two interventions

Abstract: BackgroundMany patients with end-stage renal disease (ESRD) need and want improved emotional and psychological support. Explicit attention to patients' emotional issues during consultations can help, yet renal consultants rarely address emotional problems. This qualitative study aimed to evaluate whether two different low-cost interventions could individually enable consultants to talk with patients about their emotional concerns during routine outpatient consultations.MethodOne intervention involved patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 50 publications
(55 reference statements)
0
16
0
Order By: Relevance
“…In fact, previous studies have shown that several factors are responsible for the well-being of hemodialysis patients, such as clinical (Cruz et al, 2016; F. Taylor, Combes, & Hare, 2016) and sociodemographic (Robinski, Mau, Wienke, & Girndt, 2016; Saffari et al, 2013) aspects. In addition to these factors, which have been widely discussed in the scientific literature, cultural issues and beliefs of individuals are increasing in importance in recent years.…”
mentioning
confidence: 99%
“…In fact, previous studies have shown that several factors are responsible for the well-being of hemodialysis patients, such as clinical (Cruz et al, 2016; F. Taylor, Combes, & Hare, 2016) and sociodemographic (Robinski, Mau, Wienke, & Girndt, 2016; Saffari et al, 2013) aspects. In addition to these factors, which have been widely discussed in the scientific literature, cultural issues and beliefs of individuals are increasing in importance in recent years.…”
mentioning
confidence: 99%
“…Staff training could include education focusing on patient-centred communication strategies, such as the use of open-ended questions and empathetic statements [38]. Recognising that distress can manifest itself in many ways, training could also focus on recognising the verbal and non-verbal signs that indicate a patient may be distressed; how to identify distress quickly; case scenarios about handling difficult situations, and learning from the experience of other professionals such as counsellors and psychologists.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of creating an environment where people feel comfortable to share difficult feelings was frequently highligh ted. 25,[53][54][55]75,78,80 This related to the physical environment; for example, setting the intervention in a safe space, such as the participant's home, or a private room. 25 It also 78 and communication 68 Social integration and interaction models 33,60,57,68 Therapeutic value of game play 53 Supportive-expressive models 52 Interdependence theory 33 Intimacy and relationship satisfaction 62,67 Psychoanalytic Inhibition and catharsis 53,55,79…”
Section: Facilitators and Barriers To Feasibility And Efficacymentioning
confidence: 99%
“…Continuity in chaotic illness model 78 Biographical disruption model/reconstruction of personal narrative 63,72,73,78 Health within illness model 78 Self Self-compassion 25,67,74 Self-regulation of attention 67 Self-efficacy and enablement 54,60,69,71 Non-directed client-centered approach 69,71,75 Ego-functioning, self-esteem, and tolerance of negative affect 59 referred to contextual factors, such as incorporating other soothing or positive elements that facilitate feelings of comfort 53,55 and healthcare professionals endorsing the intervention and framing it as safe and trustworthy. 54 The importance of creating a safe environment extended to ensuring that family carers felt comfortable with the participant taking part in the intervention; 33,55 this can be particularly salient in non-Western countries, such as China, where there are cultural barriers to expressing emotions. 53 Some noted that partner-based interventions improved retention and feasibility over private interventions, 62,67 suggesting the presence of a partner may contribute to feeling safe and supported.…”
Section: Life-stage and Developmentalmentioning
confidence: 99%
See 1 more Smart Citation